Experimental Study of the Slit Spacing and Bed Height on the Thermal Performance of Slit-Glazed Solar Air Heater (vol 2017, 9851376, 2017) - Mousavi, Seyed Mahdi Taheri; Egelioglu, Fuat (Hindawi Ltd, 2017)
[Abstract Not Available]